A Reevaluation of the Voluntary Medical Male Circumcision Scale-Up Plan in Zimbabwe - Awad, Susanne F. (PLoS One, 2015)
BACKGROUND: The voluntary medical male circumcision (VMMC) program in Zimbabwe aims to circumcise 80% of males aged 13–29 by 2017. We assessed the impact of actual VMMC scale-up to date and evaluated the impact of potential alterations to the program to enhance program efficiency, through prioritization of subpopulations. METHODS AND FINDINGS: We implemented a recently developed analytical approach: the age-structured mathematical (ASM) model and accompanying three-level conceptual framework to assess the impact of VMMC as an intervention. By September 2014, 364,185 males were circumcised, an initiative that is estimated to avert 40,301 HIV infections by 2025. Through age-group prioritization, the number of VMMCs needed to avert one infection (effectiveness) ranged between ten (20–24 age-group) and 53 (45–49 age-group). The cost per infection averted ranged between $811 (20–24 age-group) and $5,518 (45–49 age-group). By 2025, the largest reductions in HIV incidence rate (up to 27%) were achieved by prioritizing 10–14, 15–19, or 20–24 year old. The greatest program efficiency was achieved by prioritizing 15–24, 15–29, or 15–34 year old. Prioritizing males 13–29 year old was programmatically efficient, but slightly inferior to the 15–24, 15–29, or 15–34 age groups. Through geographic prioritization, effectiveness varied from 9–12 VMMCs per infection averted across provinces. Through risk-group prioritization, effectiveness ranged from one (highest sexual risk-group) to 60 (lowest sexual risk-group) VMMCs per infection averted. CONCLUSION: The current VMMC program plan in Zimbabwe is targeting an efficient and impactful age bracket (13–29 year old), but program efficiency can be improved by prioritizing a subset of males for demand creation and service availability. The greatest program efficiency can be attained by prioritizing young sexually active males and males whose sexual behavior puts them at higher risk for acquiring HIV.